Analysis and control of oilwell drilling vibrations : a time-delay systems approach /: a time-delay systems approach. (2015) - Márquez, Martha Belem Saldivar; Boussaada, Islam; Mounier, Hugues; Niculescu, Silviu-Iulian
No abstract available